Dielectric and impedance spectroscopic studies of (Sr1-xPb x)TiO2 glass ceramics with addition of Nb 2O5 - Gautam C.R.; Kumar D.; Parkash O.M. (My University, 2025)
Glasses were made by melt-quench method in the system [(Sr 1-xPbx)O·TiO2]-[2SiO2· B2O3]-5[K2O- BaO] (0·0 ≤ x ≤ 0·4) with addition of 1 mol% Nb2O5. Perovskite strontium lead titanate in solid solution phase has been crystallized in borosilicate glassy matrix with suitable choice of composition and heat treatment schedule. Addition of 1 mol% of Nb2O5 enhances the crystallization of lead strontium titanate phase in the glassy matrix. Scanning electron microscopy (SEM) is performed to study the surface morphology of the crystallites and crystalline interface to the glass. Dielectric properties of these glass ceramics were studied by measuring capacitance and dissipation factor as a function of temperature at a few selected frequencies. Nb2O5 doped strontium lead titanate glass ceramic shows a high value of dielectric constant. It is of the order of 10,000 while the dielectric constant of undoped glass ceramic sample is of the order of 500. Complex impedance and modulus spectroscopic techniques were used to find out the contributions of polarization of crystallites and glass crystal interfaces to the resulting dielectric behaviour. © Indian Academy of Sciences.